Conflict Management Diversity Among Faculty in a Private Medical University of Pakistan - Mirza, Tayyeba Iftikhar; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the different conflict management styles among health educators at a private medical university in Pakistan Study Design: Cross-sectional Place and Duration of Study: Foundation University School of Health Sciences, Islamabad Pakistan from May to Jul 2024. Methodology: Faculty from MBBS, BDS, Physical Therapy, and Nursing programs participated. Data was collected using a validated self-reported questionnaire, including demographic details and the Rahim Organizational Conflict Inventory-II. Descriptive statistics were calculated, and Chi-square tests were used for associations between categorical variables. The Shapiro-Wilk test assessed the normality of experience, and the Kruskal-Wallis test was applied due to non-normal distribution (p<0.001). Results: The study included 130 faculty members, predominantly female (78%). Four out of five conflict management styles were used. The collaborating style was the most common (66%), followed by avoiding (16%), compromising (13%), and accommodating (5%). None of the participants used the competing style. Age, experience, and discipline significantly influenced the preference for conflict management styles, with p-values of 0.039, 0.004, and 0.001, respectively. Gender, education, and designation showed no significant influence on the choice of conflict management style, with p-values of 0.203, 0.417, and 0.262 respectively. Conclusion: Health educators mainly use the collaborative conflict management style. A smaller number prefer avoiding or compromising, while none chose the competing style. Age, experience, and discipline significantly impact conflict management preferences, whereas gender, education and designation do not have any influence.